On the Scope of XPS as Sensor in Coordination Chemistry of Transition Metal Hexacyanometallates. Issue 13 (14th March 2019) - Cano, Arely; Rodríguez‐Hernández, Joelis; Reguera, Leslie; Rodríguez‐Castellón, Enrique; Reguera, Edilso
Abstract : This study reports an evaluation on the scope of X‐ray photoelectron spectroscopy (XPS) to obtain information for the coordination chemistry of transition metal (T n ) hexacyanometallates, T x A z [M m (CN)6 ] y where nx + z = y (6 – m ), A is an alkaline charge‐compensating cation, and M m is a transition metal with a maximum of 6 electrons in its n d orbitals. XPS provides an elegant picture on the role of the CN π‐back bonding effect to determine the charge density on the N atom and, from this fact, on its coordination to transition metal ions to form coordination polymers. XPS appears to be able to discriminate between octahedral and tetrahedral coordination for the outer metal (T) to the N end of CN ligands, particularly when the XPS peak and the Auger lines are combined. A similar performance was observed when this spectroscopic technique is used to identify when the CN ligand is found with linear and bifurcated coordination mode to the metal linked at its N end. These last two structural features are relevant in the coordination of metal hexacyanometallates and determine their physical and functional properties. The results obtained from XPS data were correlated with the a priori information from IR spectra and the reported crystal structures for all the samples under study. Abstract : A change in the coordination mode for the cyanide ligand from linear to bifurcated at its N end results in a shift of +0.3 eV for the binding energy of Cd 3d5/2 core electrons. In the Cd MNN Auger peaks the shift is of +0.5 eV. This illustrates that from a combination of XPS and Auger spectra conclusive evidence on the coordination mode for the CN ligand can be obtained.